2002
DOI: 10.1002/humu.9098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cx26/GJB2 in German hearing impaired persons: mutation spectrum and detection of disequilibrium between M34T (c.101T>C) and -493del10

Abstract: Mutations in the connexin 26 gene (GJB2) are responsible for the major part of nonsyndromic autosomal recessive or apparently sporadic prelingual deafness in Caucasians (DFNB1). We screened 228 German hearing-impaired persons for mutations in the GJB2 gene by sequence analysis. Homozygous or compound heterozygous GJB2 mutations were detected in 38/228 (16.7%) of hearing impaired persons. The most frequently occurring mutation was the c.35delG mutation, which was found in 71.1% of the mutated alleles. The next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…12,11,18,10,23,13,24 However, as Griffith et al 10 we reported here five normal hearing subjects carrying a compound heterozygous mutation in which the M34T substitution is associated in trans with a truncated mutation : the 35delG GJB2 mutation or the (GJB6-D13S1830)del. 20 These results indicate that M34T is not a recessive mutation responsible for hearing loss.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…12,11,18,10,23,13,24 However, as Griffith et al 10 we reported here five normal hearing subjects carrying a compound heterozygous mutation in which the M34T substitution is associated in trans with a truncated mutation : the 35delG GJB2 mutation or the (GJB6-D13S1830)del. 20 These results indicate that M34T is not a recessive mutation responsible for hearing loss.…”
Section: Discussionmentioning
confidence: 46%
“…Two recent reports have found a 10 base pairs deletion in the 5 0 UTR of GJB2 that occurs together with the M34T mutation. 11,24 The last one 24 have demonstrated a linkage desequilibrum between these two variants. However, in several families reported in these two studies, 11,24 neither the M34T nor the À493del10 segregated with the deafness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, comparison with other studies and their mutation detection rates is difficult with variability of study design, demographic influences and extent of analyzing methods. In relation to other German studies [45][46][47] with an estimated percentage between 6.4 and 16.7 % of patients with biallelic GJB2 mutations our level of 31.3 % is notably higher, leading us to the suggestion that the contribution of GJB2 to nonsyndromic hearing loss is may be a little overrated in German population but still the leading cause for deafness with genetic background.…”
Section: Discussionmentioning
confidence: 70%
“…This study and follow-up studies led to the identification of a homozygous mutation in the GJB2 gene in affected members of three families with autosomal recessive nonsyndromic sensorineural deafness linked to 13q11-q12 [16,64]. Today, more than 90 distinct autosomal recessive mutations of GJB2 are known, including nonsense, missense, splicing, frameshift mutations, and inframe deletions [24, 63,64,166].…”
Section: Cx47 and Pelizaeus-merzbacher-like Diseasementioning
confidence: 99%